Justice - Osborn, Kevin, 1959- (New York : Rosen Pub. Group, 1992)
Discusses the meaning of justice and gives examples of "just" behavior and its importance in life.
Includes bibliographical references (p. 62) and index.
Keywords: Justice -- Juvenile literature; Justice; Conduct of life